Association study of MMP8 gene in osteoarthritis. (2nd January 2016) - Näkki, Annu; Rodriguez-Fontenla, Cristina; Gonzalez, Antonio; Harilainen, Arsi; Leino-Arjas, Päivi; Heliövaara, Markku; Eriksson, Johan G.; Tallroth, Kaj; Videman, Tapio; Kaprio, Jaakko; Saarela, Janna; Kujala, Urho M.
ABSTRACT: Objectives : Osteoarthritis (OA) is a joint disease common in the elderly. There is a prior functional evidence for different matrix metalloproteinases (MMPs), such as MMP8 and MMP9, having a role in the breakdown of cartilage extracellular matrix in OA. Thus, we analyzed whether the common genetic variants of MMP8 and MMP9 contribute to the risk of OA. Materials and methods : In total, 13 common tagging single-nucleotide polymorphisms (SNPs) were studied in a discovery knee OA cohort of 185 cases and 895 controls. For validation, two knee OA replication cohorts and two hand OA replication cohorts were studied (altogether 1369 OA cases, 4445 controls in the five cohorts). The χ 2 test for individual study cohorts and Cochran–Mantel–Haenszel test for combined meta-analysis were calculated using Plink. Results : The rs1940475 SNP in MMP8 showed suggestive association in the discovery cohort (OR = 0.721, 95% CI 0.575–0.906; p = 0.005). Other knee and hand OA replication study cohorts showed similar trend for the predisposing allele without reaching statistical significance in independent replication cohorts nor in their meta-analysis ( p > 0.05). Meta-analysis of all five hand and knee OA study cohorts yielded a p -value of 0.027 (OR = 0.904, 95% CI 0.826–0.989). Conclusions : Initial analysis of the MMP8 gene showed suggestive association between rs1940475 and knee OA, but the finding did not replicate in other study cohorts, even though the trend for predisposing allele was similar in all five cohorts. MMP-8 is a good biological candidate for OA, but our study did not find common variants with significant association in the gene.